Penisilin Modeli Deneysel Epilepside Verapamilin Antikonvulsan Etkisi - Bağırıcı, Faruk; Gökçe, Fatih M.; Marangoz, Cafer (My University, 1999)
Epilepsi, toplumun yaklaşık %1'ini etkileyen çok yaygın bir nörolojik hastalıktır. Kalsiyum iyonları hücresel fonksiyonların düzenlenmesinde çok önemli role sahiptirler. Kalsiyum iyonlarının hücre içine girişinin epileptik nöronal olayların ilk adımını teşkil ettiğine inanılmaktadır. Sunulan çalışmada, intrakortikal penisilin uygulanması ile oluşturulan deneysel epilepsi modeline verapamilin etkisi araştırıldı. Anestezili sıçanlarda sol serebral korteks kraniotomi ile açığa çıkarıldı. Somatomotor kortekse 500 ünite penisilin G potasyum verilerek epileptik odak oluşturuldu. Aynı bölgeye verapamil (50 ve 100 µM) mikroenjeksiyonu elektrokortikogramda 5-6 dakika süreyle bir inhibisyona sebep oldu (p0.001). Bu çalışmanın sonuçları, verapamilin antikonvulsan bir ajan olabileceğini göstermektedir.

Epilepsy is a common neurological disorder that affects approximately 1% of the population. Calcium ions have important role on the regulation of cellular functions. It is believed that calcium flux into the cell is the first step of epileptic neuronal events. In present study, the effect of verapamil on experimental model epilepsy induced by intracortical (i.e.) penicillin administration was investigated. The left cerebral cortex exposed by craniotomy in anaesthetized rats. The epileptic focus was produced by injection of penicillin G potassium (500 units) into the somatomotor cortex. Microinjection of verapamil (50, 100 µM) into the same area caused an inhibition for 5-6 minutes in electrocorticograms (ECoG). (p<0.001). The results of this study suggest that verapamil may be an anticonvulsant agent.
The anticonvulsant effect of verapamil on experimental model epilepsy induced by penicillin
Keywords: Genel ve Dahili Tıp